THREE CASES OF PRIMARY MALIGNANT LYMPHOMA OF THE SPLEEN - YOSHIDA, Kazuya; SHIMA, Yoshikatsu; ISHIKAWA, Hiroshi; FUKUOKA, Hidetoshi; KAWANO, Fumiaki; IWASAKI, Keisuke (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2002)
Primary malignant lymphoma of the spleen is relatively rare and present difficulty in making the qualitative diagnosis. We often make its definite diagnosis after surgical removal. This paper describes three cases of primary malignant lymphoma of the spleen treated in the hospital together with some bibliographical comments. Subjects were three cases of primary malignant lymphoma of the spleen operated on at the hospital from April 1993 to March 2000. Their age is relatively high, ranged from 69 to 73. The male-to-female ratio was two to one. One case of them was diagnosed as primary malignant lymphoma of the spleen before operation. All of them, pathological diagnosis is malignant lymphoma, diffuse large cell, B cell type. Splenectomy was made in all cases, including one case of associated resection of pancreatic tail and one case of associated resection of pancreatic body and tail with a partial gastrectomy. All patients were given postoperative chemotherapy. Two patients of them are alive without recurrence, however, one patient died within one year after the operation. Ga-scintigraphy is useful for diagnosis of primary malignant lymphoma of the spleen. Overall treatment with surgical excision is necessary for this disease.